Gesture recognition based on hand postures and trajectories by using dataglove: A fuzzy probability approach – A review - Wan Khairunizam, Wan Ahmad, Dr; Nazrul Hamizi, Adnan; Shahriman, Abu Bakar, Dr.; Siti Khadijah, Za’ba, Dr.; Mohd Azri, Abd Aziz (Universiti Malaysia Perlis (UniMAP), 2012)
International Conference on Man Machine Systems (ICoMMS 2012) organized by School of Mechatronic Engineering, co-organized by The Institute of Engineer, Malaysia (IEM) and Society of Engineering Education Malaysia, 27th - 28th February 2012 at Bayview Beach Resort, Penang, Malaysia.